Morte e poder: o Mosteiro da Batalha e a construção da memória funerária de Avis no contexto Ibérico (Século XV) - Azevedo, Hugo Rincon (2021)
The Dynasty of Aviz established in the government of King John I as the ruler of Portugal in 1385, had throughout the 15th and early 16th centuries an intense concern with the construction and preservation of the royalty memory. Be it the crystallization of memory produced through written documents, such as royal chronicles or through monuments, such as the Santa Maria da Vitória Monastery. Built on the outskirts of Aljubarrota (1385), the monastery became a royal pantheon, a place of memory and symbol of power when it withheld the remains of kings and members of the reigning house. In this way, the medieval period saw the old conception of "good death" transformed into a Christianized death at different rates, which shaped the customs of dying in an attempt to control it by the individual, with the mediation of the Church, through the necessary rituals for the guarantee to the salvation of the soul. The cult of the dead has become the main mechanism for celebrating the memory of death, which, along the adoption of these practices by the aristocracy, has become a great manifestation of power. In the last centuries of the Middle Ages, monarchies appropriated those conceptions, resulting in the production of dynastic and secular histories destined to legitimize the power of princes. In Portugal between the 15th and 16th centuries, the chroniclers of the House of Aviz built speeches idealizing the passing of the monarchs of the dynasty. We analyzed the narratives about the kings of Aviz (John I, Edward I, Afonso V and John II) and the members of the royal family (Queen Philippa of Lancaster and the princes of the "Illustrious Generation") buried in Batalha Monastery. We problematize the relations between the idealization of the death of these kings present in the narratives and in the ceremonial produced in memory of their deaths. To understand this process, we resort to the Comparative History method. We chose as comparative analysis objects the chronistic speeches of the death of the kings of Aviz in Portugal and of Trastámara in Castile in the 15th century, along with the construction of funerary monuments as symbols of legitimation and dynastic propaganda